Poemas al servicio de los grupos dominados: la identidad (afro)cubana y la poesía de Nicolás Guillén - Szymoniak, Ewelina (Romanica Silesiana)
What characterizes Latin American literature starting from the 19th century, after gaining independence, is, without a doubt, the search for its own unique features. Scientists, thinkers, novelists and poets have been trying to provide Latin American people with the consciousness of their own identity, defined, in most cases, in terms contradictory to those used in Europe or the United States. The aim of this paper is to present how, in this context, Nicolás Guillén, an Afro-Caribbean poet, builds a concept of (Afro)Cubanism (or Americanism, as his theses apply to the entire region). Given the assumption that identity is a project of a reflexive character (Giddens), and that discourse determines the relation between power, knowledge and identity (Foucault), the paper analyzes the poetry of Nicolás Gullén in the light of various concepts from the field of cultural studies, including ethnic absolutism, creative geographies, transculturation/acculturation, ideology, hegemony and symbolic violence. Key words: Nicolás Guillén — identity — (Afro)Cuban — cultural studies.